On fixed points for for alpha–eta–psi-contractive multi-valued mappings in partial metric spaces - La Rosa, Vincenzo; Vetro, Pasquale (Nonlinear Analysis: Modelling and Control, 2015)
Recently, Samet et al. introduced the notion of α–ψ-contractive type mappings and established some fixed point theorems in complete metric spaces. Successively, Asl et al. introduced the notion of α*–ψ-contractive multi-valued mappings and gave a fixed point result for these multi-valued mappings. In this paper, we establish results of fixed point for α*-admissible mixed multi-valued mappings with respect to a function η and common fixed point for a pair (S,T) of mixed multi-valued mappings, that is, α*-admissible with respect to a function η in partial metric spaces. An example is given to illustrate our result.
Keywords: partial metric space; α–η–ψ-contractive condition; α*-admissible pair with respect to a function η; fixed point; common fixed point